Predictors of mean arterial pressure morning rate of rise and power function in subjects undergoing ambulatory blood pressure recording. - Geoffrey A Head (Public Library of Science (PLoS), 2014)
Background We determined clinical predictors of the rate of rise (RoR) in blood pressure in the morning as well as a novel measure of the power of the BP surge (BP(power)) derived from ambulatory blood pressure recordings. Methods BP(power) and RoR were calculated from 409 ambulatory blood pressure (ABP) recordings from subjects attending a cardiovascular risk clinic. Anthropometric data, blood biochemistry, and history were recorded. The 409 subjects were 20-82 years old (average 57, SD = 13), 46% male, 9% with hypertension but not on medication and 34% on antihypertensive medication. Results Average RoR was 11.1 mmHg/hour (SD = 8) and BP(power) was 273 mmHg(2)/hour (SD = 235). Only cholesterol, low density lipoprotein and body mass index (BMI) were associated with higher BP(power) and RoR (P<0.05) from 25 variables assessed. BP(power) was lower in those taking beta-blockers or diuretics. Multivariate analysis identified that only BMI was associated with RoR (4.2% increase/unit BMI, P = 0.020) while cholesterol was the only remaining associated variable with BP(power) (17.5% increase/mmol/L cholesterol, P = 0.047). A follow up of 213 subjects with repeated ABP after an average 1.8 years identified that baseline cholesterol was the only predictor for an increasing RoR and BP(power) (P<0.05). 37 patients who commenced statin subsequently had lower BP(power) whereas 90 age and weight matched controls had similar BP(power) on follow-up. Conclusions Cholesterol is an independent predictor of a greater and more rapid rise in morning BP as well as of further increases over several years. Reduction of cholesterol with statin therapy is very effective in reducing the morning blood pressure surge.